2021
DOI: 10.12776/qip.v25i2.1559
|View full text |Cite
|
Sign up to set email alerts
|

Improving Team Collaboration in Patient Transfer Processes by Co-Workers’ Perceptions and Suggestions

Abstract: Purpose: The purpose was twofold: first to describe how co-workers within a team perceived team collaboration in patient transfers from an intensive care unit (ICU) to general wards and, second, to describe co-workers’ suggestions for an improved future state of team collaboration. Methodology/Approach: Focus group discussions (FGDs) were conducted at two medium-sized hospitals located in Sweden. Participants were multidisciplinary and from both ICUs and general wards. Data were analysed using qualitative dedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Implementing regular patient safety huddles (Fencl and Willoughby, 2019) and interdisciplinary team care interventions with staff from the ICU and general wards could be solutions to improve patient safety and quality of care and focus on the customer (patient and/or relatives). This is in line with Sten et al (2021), who found that coworkers want to involve patients and relatives in improving team collaboration when seeking quality care.…”
Section: Analysis and Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Implementing regular patient safety huddles (Fencl and Willoughby, 2019) and interdisciplinary team care interventions with staff from the ICU and general wards could be solutions to improve patient safety and quality of care and focus on the customer (patient and/or relatives). This is in line with Sten et al (2021), who found that coworkers want to involve patients and relatives in improving team collaboration when seeking quality care.…”
Section: Analysis and Discussionsupporting
confidence: 83%
“…Furthermore, delays in the patient transfer process can be reduced by early evaluation, timely team communication, and proper preparation (Alali et al, 2019;De Grood et al, 2018). Also, involving and communicating decisions to the whole team and across organisational boundaries can avoid the perception of 'parallel systems' (Sten et al, 2021).…”
Section: Analysis and Discussionmentioning
confidence: 99%